2015
DOI: 10.1103/physrevlett.115.161101
|View full text |Cite
|
Sign up to set email alerts
|

Compactness of Neutron Stars

Abstract: Recent progress in the determination of both masses and radii of neutron stars are starting to place stringent constraints on the dense matter equation of state. In particular, new theoretical developments together with improved statistical tools seem to favor stellar radii that are significantly smaller than those predicted by models using purely nucleonic equations of state. Given that the underlying equation of state must also account for the observation of 2M neutron stars, theoretical approaches to the st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
159
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(169 citation statements)
references
References 30 publications
10
159
0
Order By: Relevance
“…Both hadronic and hybrid star radii of 1.4 M are above 12.8 km, within the observations of the objects BNS 4U 1608−522 [61], BNS SAX J1748.9−2021 [62,63], and RP-MSP PSR J0437−4715 [64,65], but out of the range 10.1-11.1 km obtained in [66], from the analysis of spectroscopic radius measurements of twelve neutron stars obtained during thermonuclear bursts or in quiescence. However, in [67], it was shown that in order to prevent the EOS from violating causality, the radius should satisfy R 1.4 10.7 km, if it is imposed that the EOS also describes a 2 M star. In [45], taking experimental constraints and causality restrictions for large maximum masses, the 1.4 M star radii were constrained to be within the interval 12.1 ± 1.1 km (see [68]).…”
Section: Discussionmentioning
confidence: 99%
“…Both hadronic and hybrid star radii of 1.4 M are above 12.8 km, within the observations of the objects BNS 4U 1608−522 [61], BNS SAX J1748.9−2021 [62,63], and RP-MSP PSR J0437−4715 [64,65], but out of the range 10.1-11.1 km obtained in [66], from the analysis of spectroscopic radius measurements of twelve neutron stars obtained during thermonuclear bursts or in quiescence. However, in [67], it was shown that in order to prevent the EOS from violating causality, the radius should satisfy R 1.4 10.7 km, if it is imposed that the EOS also describes a 2 M star. In [45], taking experimental constraints and causality restrictions for large maximum masses, the 1.4 M star radii were constrained to be within the interval 12.1 ± 1.1 km (see [68]).…”
Section: Discussionmentioning
confidence: 99%
“…Although there is not still an accurate enough determination of NS radii, we have considered the constraint imposed by two recent studies on NS: a lower limit of R > 10.7 km for NS with masses M = 1.4 M established by Chen & Piekarewicz (2015), and an upper limit of R < 16.8 km, inferred from the NS RX J1856-375 Boshkayev et al (2016). The radii obtained for the CHS are within the range set by such limits.…”
Section: Structure Of Hybrid Starsmentioning
confidence: 99%
“…According to Ref. [7], an EOS with M max > 2M should produce R 1. 4 10.7 km in order to avoid being noncausal at highest NS densities.…”
Section: Introductionmentioning
confidence: 99%